Needle Stick Injuries, Sharp Injuries and other Occupational Exposures to Blood and Body Fluids among Health Care Workers in a general hospital in Sarajevo, Bosnia and Herzegovina - Musa, Sanjin; Peek-Asa, Corinne; Young, Tracy; Jovanović, Nina (International Journal of Occupational Safety and Health, 2015)
Correction: On 2nd January 2018, the following authors were added to the online version of this article: Corinne Peek-Asa, Tracy Young and Nina Jovanović. They were always on the PDF of the article. The editor apologises for this error. Background: Professional exposures of health care workers (HCW) to potentially infective blood and body fluids presents a serious health threat, including hepatitis B, hepatitis C and HIV transmission. This study was conducted to assess the risk for and reporting of needlestick injuries, sharp injuries and other occupational exposures of health care workers in a large healthcare center in Sarajevo. Methods: This cross-sectional survey was conducted in May 2013. The study target population included all hospital health care workers who had a high potential for exposure. The estimated sample size was 48 physicians, 132 nurses/technicians and 30 auxiliary personnel. Results: During their career, 124 (63.3%) HCW reported exposures to blood and body fluids. In total, needle stick injuries (66.1%) were the most common source of exposure, followed by contact with intact skin (12.1%) and cut with sharp object (11.3%). Only 43 (35.5%) reported any of these exposures to health authorities during their career. The odds of exposure to needle stick injuries and other occupational exposures to blood and bodily fluids were significantly higher among medical nurses/techicians (AOR=4.98, 95%CI=1.52-16,1) and auxillary (AOR=4.30, 95%CI=1.07-17.34) personnel when compared to physicians. HCW in the operation room, intervention ambulance and laboratory (AOR=3.73, 95%CI=1.43-9.72) had higher odds of exposure than workers in the ambulatory departments. Conclusions: Needlestick Injuries, Sharp Injuries and other Occupational Exposures to Blood and Body Fluids among health care workers are underestimated hazard. Especialy, for HCW who work in operation room/interventional ambulance. There is a need for preventive programs for HCW and further work on the establishment of an effective surveillance system.